Analysis of hygienic habits and prophylactic measures applied by pregnant women - Komsta, Aneta; Hendzel, Barbara (Polish Journal of Public Health, 2011)
Introduction. The incidence of dental caries and periodontal diseases as social phenomena has been studied and monitored as for all sorts of age groups, depending on the sex, the region of living and the social status of the studied subjects. The evaluation of oral health in pregnant women is important, since it regards the health of the woman in this special period of her life. Aim. The analysis of hygienic habits and preventive actions applied by pregnant women was a purpose of the work. Material and methods. There were 325 pregnant women aged 18-38 included in the research. The methods of the standardized interview were used along with the interview questionnaire with questions concerning the knowledge of correct health behaviours, hygienic and dietary habits. Results. Out of the studied population, 17.2% were using dental services less frequently than once a year. Only 34.5% of patients referred to the dentist at least once a year. In the group of the studied patients 58.8%, were brushing teeth twice a day, 29.8% of individuals – once a day, and three times a day was common with as little as 10.2% of the respondents. After each meal only 4.6% of patients brush their teeth and as much as 95.4% of respondents don’t brush their teeth after each meal. The sugar-rich diet significantly influences the incidence of the dental caries. Over half of the studied women (58.5%) consumed sweets more often than 4 times during the week, and a little bit smaller group (35.4%) ate sweets 3-4 times during the week. Majority of the studied patients (59.4%) reported that during pregnancy they had eaten sweets more often than before this period. Conclusions. The findings showed no adherence to the principles of the dental hygiene or to pro-health behaviours in the studied population of pregnant women which has significant influence on the medical condition of the stomatognathic system and the whole body.